Women and Christianity - Kirk-Duggan, Cheryl A.; Torjesen, Karen Jo (Women and religion in the world., 2010)
This work explores the impact of Christian women-as scholars and leaders representing the ethnic, national, racial, and denominational diversity of Christianity today-on all aspects of life. * Includes 15 essays from contributors who represent a mix of established and young, emerging, and innovative scholars, all of whom are working for change in their faith communities * A bibliography accompanies each essay